Translating Chinese culture the process of Chinese-English translation - Pellatt, Valerie; Liu, Eric; Chen, Yalta Ya-Yun (London Routledge/Taylor & Francis Group, 2014)
"Translating Chinese Culture is an innovative and comprehensive coursebook which addresses the issue of translating concepts of culture. Based on the framework of schema building, the course offers helpful guidance on how to get inside the mind of the Chinese author, how to understand what he or she is telling the Chinese-speaking audience, and how to convey this to an English speaking audience. A wide range of authentic texts relating to different aspects of Chinese culture and aesthetics are presented throughout, followed by close reading discussions of how these practices are executed and how the aesthetics are perceived among Chinese artists, writers and readers. Also taken into consideration are the mode, audience and destination of the texts. Ideas are applied from linguistics and translation studies and each discussion is reinforced with a wide variety of practical and engaging exercises. Thought-provoking yet highly accessible, Translating Chinese Culture will be essential reading for advanced undergraduates and postgraduate students of Translation and Chinese Studies. It will also appeal to a wide range of language studies and tutors through its stimulating discussion of the principles and purposes of translation"-- Provided by publisher.
Includes bibliographical references (pages 174-185) and index.
Keywords: Chinese language -- Translating into English; Language and culture -- China; China -- Languages